Common Diagnoses among Refugee Populations: Linked Results with Statewide Hospital Discharge Database - Kerui Xu; Shinobu Watanabe-Galloway; Ming Qu; Brandon Grimm; Jungyoon Kim (Ubiquity Press, 2018)
Background: According to the U.S. State Department's Refugee Processing Center and the U.S. Census Bureau, in the fiscal year 2016, among all states in the United States, Nebraska resettled the highest number of refugees per capita. Objectives: The objectives of this study were to determine the most common reasons for refugees utilizing hospital services in Nebraska between January 2011 and September 2015, and to examine whether refugee patients had increased risks for adverse health conditions compared to non-refugee patients. Methods: Statewide linkage was performed between Nebraska Medicaid Program's immigration data, and 2011-2015 Nebraska hospital discharge data inpatient and outpatient files. The linkage produced 3017, 5460, and 775 cases for emergency department visits, outpatient clinic visits, and inpatient care for the refugee sample, respectively. Findings: Refugee patients were at increased risk for a number of diagnoses or medical conditions, including pregnancy complications, abdominal pain, upper respiratory infections, viral infections, mood disorders, disorders of teeth and jaw, deficiency and anemia, urinary system disorders, headache, nausea and vomiting, limb fractures, spondylosis, essential hypertension, and uncomplicated diabetes mellitus. Conclusions: The findings suggest a greater emphasis on preventive healthcare, especially in areas of maternal health and perinatal outcomes, psychological counseling, screening for infectious diseases, nutrition and healthy eating, and oral health. Additionally, culturally appropriate measures to address prevention, health screening, and treatments should be adopted by health providers who care for refugees.